DILEMMA IN EXPLOITING MEDIA TECHNOLOGY IN ELT: BETWEEN OPPORTUNITY AND CHALLENGE - Anton Suratno (Soegijapranata Catholic University, 2003)
Since the turn of the twentieth centU/y. sophisticated technologies have marked the revolutionary era of human beings. The rate of the progress is so incredible that 110 one is able to predict what other changes may be happening. Despite being late. ELTworld has slowly begun to change by adopting media technologies in teaching. During the course of the change, however; the practicioners of the technologies pose a dilemma in the level of implementatioll. Oil the one hand, they offer grand opportunities to create a brighter future, but on the other hand, they bring with them challenges that may prevent the teacher practicionersfrom adopting thelll il/lal/guage teaching practices. Thus, it is within this perspective that this paper is trying to discuss by viewing them from what the opportunities alld the challenges it poses by offer inga way outfrom it. This paper will mainly be a reflective discllssion ill nature, as it tries to open lip those m'o opposing sides alld underlines the potentially remaining problems that may intact if they are not coped with ill a proper manner.